Health Risk Behaviors and Associated Factors Among Hajj 2024 Pilgrims: A Multinational Cross-Sectional Study - Samarkandi O; Alamri FA; Alhazmi J; Alsaleh GS; Alsehdwei KA; Alabdullatif L; Alazmy W; Khan A (Risk Management and Healthcare Policy)
Osama Samarkandi,1 Fahad Abdulrahman Alamri,2 Jumanah Alhazmi,2 Ghadah Sulaiman Alsaleh,2 Kwather Atteyah Alsehdwei,3 Lames Alabdullatif,2 Waleed Alazmy,1 Anas Khan4 1Department of Basic Science, Prince Sultan College for Medical Emergencies, King Saud University, Riyadh, Saudi Arabia; 2Global Center for Mass Gathering Medicine (GCMGM), Ministry of Health, Riyadh, Saudi Arabia; 3Ministry of Health, Department of Medicine, Riyadh, Saudi Arabia; 4Department of Emergency Medicine, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Osama Samarkandi, Department of Basic Science, Prince Sultan College for Medical Emergencies, King Saud University, Riyadh, Saudi Arabia, Email osamarkandi@KSU.EDU.SABackground and Objective: The Hajj, a massive annual pilgrimage to Mecca, attracts over 2 million participants. The physically demanding rituals, extreme heat, and crowding increase the risk of injuries worsen chronic conditions, and facilitate infectious disease transmission. Therefore, this study aims to assess the risk behavior and associated factors among pilgrims during the Hajj season of 2024.Methods: A cross-sectional study was conducted among pilgrims during the Hajj season from June 25 to July 30, 2024. The data were randomly collected from departures at Jeddah’s King Abdulaziz International Airport and analyzed using the Statistical Package for the Social Sciences (SPSS).Results: Out of the 1183 pilgrims, 47.5% were male (n=562). The mean age was 54.98± 13.96. Risky behaviors were common among pilgrims: 26.9% (n = 318) did not use umbrellas in direct sunlight, and 49.6% preferred walking over using transportation. Additionally, 51.7% did not take prescribed medication, and 59.9% did not seek urgent care for severe symptoms. The mean risk-taking behavior score was 3.24± 1.05, with 36.6% of pilgrims exhibiting high-risk behavior and 63.4% exhibiting low-risk behavior. Significant associations were found between risk behavior and education (χ² = 96.502, p < 0.001), nationality (χ² = 69.681, p < 0.001), and certain health conditions (asthma, hearing and vision impairment, and heart disease). Multiple linear regression identified gender (B=0.218, SE=0.059, CI=0.102 to 0.334, p< 0.001), education (B=− 0.044, SE=0.019, CI=− 0.082 to − 0.006, p=0.023), nationality (B=− 0.168, SE=0.024, CI=− 0.215 to − 0.122, p< 0.001), presence of vision impairment (B=− 3.177, SE=1.429, CI=− 5.981 to − 0.372, p=0.026), and heart disease (B=2.118, SE=1.013, CI=0.130 to 4.106, p=0.037) as predictors of risky behavior (p< 0.001).Conclusion: Minor risk behaviors among pilgrims can lead to increased morbidity, mortality, and logistical challenges. Guidance promoting healthy practices before and during the pilgrimage is essential to mitigate these risks and reduce adverse outcomes.Keywords: risk behaviours, physical activity, chronic diseases, direct sunlight